Financial versus monetary mercantilism-long-run view of large international reserves hoarding - Joshua Aizenman; Jaewoo Lee (University of California, Economics Department, 2006)
The sizable hoarding of international reserves by several East Asian countries has been frequently attributed to a modern version of monetary mercantilism - hoarding international reserves in order to improve competitiveness. From a long-run perspective, manufacturing exporters in East Asia adopted financial mercantilism-subsidizing the cost of capital- during decades of high growth. They switched to hoarding large international reserves when growth faltered, making it harder to disentangle the monetary mercantilism from precautionary response to the heritage of past financial mercantilism. Monetary mercantilism also lowers the cost of hoarding, but may be associated with negative externalities leading to competitive hoarding.
Keywords: F15; F31; F43; 330; Mercantilism; cost of capital; competitive real depreciations; self insurance; precautionary hoarding; Währungsreserven; Internationaler Wettbewerb; Wirtschaftswachstum; Merkantilismus; Ostasien